Review on adolescent pregnancy and social implications: Revisión sobre el embarazo adolescente e implicancias sociales - Cevallos Mendoza, Milena Elizabeth (2024)
This study reviews the social implications of teenage pregnancy and identies the factors that contribute to its incidence among adolescents aged ten to nineteen in Latin America. The review follows the PRISMA guidelines for conducting a literature review. The article search was conducted in PubMed, using keywords related to teenage pregnancy, causes, and prevention. A total of 411 articles were identied, of which 20 met the inclusion criteria: studies based in Latin America, published since 2010, and focused on the prevention of teenage pregnancy. The main results show that the lack of sexual education and ignorance about contraceptive methods are key factors in the incidence of teenage pregnancy. Socioeconomic factors such as poverty and inequality also play a signicant role. Domestic violence and the early onset of sexual activity are other critical factors. Additionally, the lack of access to health services and adequate education is highlighted. Teenage pregnancy is a biopsychosocial problem with serious repercussions. It is necessary to improve sexual education and access to contraceptives to prevent teenage pregnancy. Interventions should be intersectoral, involving the family, community, educational system, and health professionals. Only through coordinated action can the incidence of teenage pregnancy be effectively reduced and its negative consequences on the health and socioeconomic development of adolescents be mitigated.